World Economic Outlook, September 2005 : Building Institutions. (World Economic Outlook; World Economic Outlook ;, 2005)
The World Economic Outlook, published twice a year in English, French, Spanish, and Arabic, presents IMF staff economists' analyses of global economic developments during the near and medium term. Chapters give an overview of the world economy; consider issues affecting industrial countries, and economics in transition to market; and address topics of pressing current interest. Annexes, boxes, charts, and an extensive statistical appendix augment the text.